PERANAN EKUITAS MEREK TERHADAP LOYALITAS KONSUMEN PRODUK HANDPHONE NOKIA (Studi pada Mahasiswa Unisbank Semarang) - Arles Nurdiansah, 08.05.51.0092; Sutedjo, Bambang (Students Journal of Economic and Management, 2012)
This research is a study of brand nokia mobile products, where brand products are assessed based on consumer perceptions of equity and its impact on consumer loyalty. Data were collected through questionnaire method against 125 peoples in the area of consumer Nokia at Faculty of Economics, Stikubank University obtained by using purposive sampling technique. From the regression analysis obtained by the equation Y = 0.123 X1 + 0.158 X2 + 0.831 X3 + 0.151 X4. Most impact on consumer loyalty that Perceived quality variable (X3), which has a coefficient of 0.831. next followed by the variable brand association (X2) with a coefficient of 0.158. brand loyalty variable (X4) with a coefficient of 0.151. For independent variables that have the smallest influence is brand awareness variable (X1) with a coefficient of 0.123. Hypothesis testing using the F test indicated that four independent variables under study is found to significantly influence the consumer loyalty. Then through a t test showed that four independent variables under study is found to significanly influence the consumer loyalty too. Therefore Figures Adjusted R square of 73,1 percent showed that consumer loyalty can be explained by fourth indipendent variables in the regression equation. While the rest of 26,9 percent is explained by others variables outside of the four variables used in this study.Keywords: Dimention of brand equity and consumer loyalty